Skin bacteriota ameliorates androgenetic alopecia via harmonizing skin immuno inflammatory balance - Yichen Cao; Xusheng Wu; Zixuan Huang; Chen Xu; Zengyan Ge; Yixin Xie; Lan Wu; Ying Qian; Bin Ding; Hongbin Luo (Brazilian Journal of Microbiology, 2026)

Differential adsorption and diffusion mechanism of CO2 in clay slit pores: Implications for structural control on geological sequestration - Yichen Wang; Yang Wang; Hongfei Cheng; Ziwei Ding; Ni He (Applied Clay Science, 2026)

Impact of acetylated konjac glucomannan on dough quality and improvement mechanism - Mingyang Fang; Xiaomin Wang; Yichen Yao; Wenping Ding; Beibei Ding; Xuedong Wang (Food Hydrocolloids, 2026)

Biofabrication and artificial intelligence strategies for investigating solid- and fluid-pressure mechanobiology in pancreatic ductal adenocarcinoma - Yahui Ding; Peiyuan Zhao; Yan Jin; Yan Li; Zifei Wang; Ye Lu; Yichen Zhang; Hongzhuan Chen; Weidong Zhang; Xin Luan; Min Tang (Cancer and Metastasis Reviews, 2026)

Possible inter-room aerosol-mediated COVID-19 transmission in a quarantine hotel: A case study - Merrill LIM; Junjing YANG; Sze Tat TAN; Man XIAO; Chun Ping GAO; Vernon LEE; Yee Leong TEOH; James CHAN; Lin CUI; Yichen DING; Joanna SHEN; Ruixin LI; et al. (Building and Environment, 2026)

Unsteady Cavitation Flow Characteristics Around the Clark-Y Hydrofoil Cascade - Wenchun Bao; Yichen Zhu; Yule Ding; Mindi Zhang; Fu Chen (Journal of Marine Science and Engineering, 2026)
Both experimental and numerical studies were conducted to obtain the influence laws of complex cavitation flow structures around a Clark-Y hydrofoil cascade. The similarities and differences in cavitation flow characteristics between the cascade and single hydrofoil were compared to analyze the influence of the cascade configuration on the flow field structure. This study focuses on the correlations among cavity development, lift–drag characteristics, and flow field features of the hydrofoil cascade. The results indicate significant differences in the development degree and history of cavities at different positions within the cascade. The top layer of the cascade exhibits a cavitation pattern similar to a single hydrofoil; both generate large-scale shedding vortices at the trailing edge. In contrast, the cavitation phenomena in the middle and bottom layers are similar to each other. The suction side of the top-layer hydrofoil influences the middle and bottom layers. This interaction suppresses the formation of large-scale shedding bubbles and subsequently hinders re-entrant shocks. Furthermore, the cavities in the middle and bottom layers develop more rapidly, causing the dynamic characteristics of the cascade to reach their peak values earlier. At the cloud cavitation stage, the Strouhal numbers (St) for cavity collapse on the top and bottom hydrofoils are approximately 0.2 and 0.3, respectively. The St for the middle hydrofoil exhibits an intermediate value that decreases from 0.3 to 0.2 as the cavitation number (σ) declines, reflecting a transitional characteristic modulated by the cascade structure. Compared to a single hydrofoil, the cascade is subject to the combined effects of the three-layer hydrofoils; consequently, its lift is approximately three times that of a single hydrofoil, though its drag also increases threefold. The lift variation pattern of the top-layer hydrofoil in the cascade is similar to that of a single hydrofoil. In contrast, the middle-layer hydrofoil exhibits a more complex lift evolution, as both its suction and pressure sides are significantly influenced by the surrounding cascade structure. For the bottom-layer hydrofoil, the lift remains relatively low because no cavities are generated on its surface. Lift fluctuation frequencies that aligned with cavity collapse were identified at 45 Hz, 70 Hz, and 50 Hz across the top, middle, and bottom cascade layers, respectively.

Integrative Assessment of Interrelated Swimming Performances and their Physiological Basis in Large Yellow Croaker (Larimichthys crocea) - Wei Liu; Junjia Zeng; Jiaxing Liu; Tingsen Jiang; Yacheng Deng; Pengxin Jiang; Yin Li; Ningyuan Ding; Yichen Li; Yujia Chen; Chuan Deng; Haojie Li; et al. (Marine Biotechnology, 2026)

Synthesis, characterization, and in vitro hypolipidemic mechanisms of sugar-SA triazole conjugates as potent pancreatic lipase inhibitors - Ruge Cao; Jingxin Li; Yue Sun; Yichen Li; Xiao-Lin Zhang; Han Ding; Xue-Wei Liu (Food Chemistry, 2025)

Ethylene glycol conversion to glycolic acid in Escherichia coli: Leveraging transcriptomic data for enhanced productivity - Yichen Gong; Wenlong Yan; Fei Liu; Mingzhu Ding; Yingjin Yuan (Journal of Environmental Chemical Engineering, 2025)

Photothermally inducing SnS2 phase transition in Cu2O@CuS@SnS2 core–shell heterostructure to trigger efficient photocatalytic CO2 reduction - Yaqi Liu; Yichen Liu; Guicheng Luo; Wentao Zhu; Ning Li; Yi Song; Huaju Song; Yun Shan; Qifan Wu; Yanan Ding; Aiping Liang; Lizhe Liu (Chemical Engineering Journal, 2025)

MAPK signaling pathway enhances tolerance of Mytilus galloprovincialis to co-exposure of sulfamethoxazole and polyethylene microplastics - Yanan Di; Liya Li; Jianzhou Xu; Ao Liu; Ruoxuan Zhao; Shuimei Li; Yichen Li; Jiawei Ding; Siyu Chen; Mengjie Qu (Environmental Pollution, 2024)

Lanthanide-doped enhances Ni-Sb-SnO2 orbital hybridization: Promoting efficient electrochemical ozone production and chlorine evolution reaction - Yufeng Xue; Jinglei Si; Jinfu Cai; Zaixiang Xu; Yuhang Wang; Yabing Wang; Mingzhe Xue; Yang Ding; Yichen Gu; Yunyi Cao; Shibin Wang; Haoqiang Cao; et al. (Chemical Engineering Journal, 2024)

Topological surface states in quasi-two-dimensional magnetic kagome metal EuTi3Bi4 - Zhicheng Jiang; Tongrui Li; Jian Yuan; Zhengtai Liu; Zhipeng Cao; Soohyun Cho; Mingfang Shu; Yichen Yang; Zhikai Li; Jiayu Liu; Jianyang Ding; Zhonghao Liu; et al. (Science Bulletin, 2024)

Deep graph learning for the fast prediction of the wake field of DARPA SUBOFF - Yichen Hao; Jiaqi Ding; Chao Bian; Pu Zhao; Linsheng Xia; Xiaofang Wang; Haitao Liu (Ocean Engineering, 2024)

A novel piezoelectric fenton-like process mediated by FeOCl for efficient contaminant removal - Yichen Ding; Hao Tao; Zeyu Guan; Fan Yang; Dongya Li (Chemical Engineering Journal, 2024)

Functionalized MOF enables stable cycling of nickel-rich layered oxides for lithium-ion batteries - Qiao Hu; Guangming Han; Aiping Wang; Kaidi Gao; Jiaying Liao; Meili Ding; Yichen Zhou; Robert Dominko; Huanting Wang; Jianfeng Yao (Chemical Engineering Journal, 2024)

Molecular simulation of CO2 adsorption on kaolinite: Insights into geological storage of CO2 - Yichen Wang; Ziwei Ding; Zhou Cao; Fangchun Han; Yang Wang; Hongfei Cheng (Applied Clay Science, 2024)

Confinement effect of FeMOFs glass enhances the proton coupled electron transfer reaction for the organic pollutants polymerization toward sustainable water purification - Shiyu Zuo; Yichen Ding; Haoshan Cheng; Zeyu Guan; Xiaohu Li; Dongya Li (Chemical Engineering Journal, 2024)

Bacterial structures and their associated ARGs in Shanghai subway air, China - Lijun Zhang; Xiaojing Li; Yongping Liu; Yi Zheng; Lisha Shi; Yichen Ding; Jian Chen; Ping Xiao (Journal of Aerosol Science, 2024)

Exploring metal(loid)s dynamics and bacterial community shifts in contaminated paddy soil: Impact of MgO-laden biochar under different water conditions - Yan Wang; Yichen Wang; Suhan Ma; Kankan Zhao; Fenghua Ding; Xingmei Liu (Environmental Pollution, 2024)

Influence of overcooking on in vitro digestion and fermentation of ground beef and whole wheat bread - Wensheng Ding; Sujun Liu; Qinnan Yang; Yichen Bai; Carmen E. Perez-Donado; Devin J. Rose (Food Research International, 2024)

Microphysical and dynamic evolution of convection observed by polarimetric radar under the influence of cloud seeding - Hepeng Zheng; Yun Zhang; Yichen Chen; Deping Ding; Zuhang Wu; Mengyu Huang; Hui He; Xincheng Ma; Zeming Zhou (Atmospheric Research, 2024)

Role of Tim-3 in COVID-19: a potential biomarker and therapeutic target - Haodong Ma; Shengju Ren; Qingpeng Meng; Boyuan Su; Kun Wang; YiChen Liu; Junpeng Wang; Degang Ding; Xin Li (Archives of Virology, 2023)

Revealing the synergistic mechanism of the generation, migration and nearby utilization of reactive oxygen species in FeOCl-MOF yolk-shell reactors - Shiyu Zuo; Yichen Ding; Li Wu; Fan Yang; Zeyu Guan; Su Ding; Dongsheng Xia; Xiaohu Li; Dongya Li (Water Research, 2023)

Liquid water determination by airborne millimeter cloud radar and in-situ size distribution measurements - Dongfei Zuo; Dantong Liu; Delong Zhao; Ling Yang; Yichen Chen; Wei Zhou; Mengyu Huang; Hui He; Ping Tian; Yuanmou Du; Wei Xiao; Ruijie Li; et al. (Atmospheric Research, 2023)

Flexural Toppling Mechanism and Stability Analysis of an Anti-dip Rock Slope - Bingdong Ding; Zhangyi Han; Guangcheng Zhang; Xingtao Beng; Yichen Yang (Rock Mechanics and Rock Engineering, 2021)

Simulating Developmental Cardiac Morphology in Virtual Reality Using a Deformable Image Registration Approach - Arash Abiri; Yichen Ding; Parinaz Abiri; René R. Sevag Packard; Vijay Vedula; Alison Marsden; C.-C. Jay Kuo; Tzung K. Hsiai (Annals of Biomedical Engineering, 2018)